Feasibility Study of Solar Power Massive Usage in Indonesia: Yield versus Cost-Effective - M A Setiawan (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2009)
The aim of this study is to analyze the cost production of solar power utilization comparing with its annual yield especially in Indonesia. Solar cell module employed is poly-crystalline silicone with Peak Power 20 Wp, Power Current (Imp) 1.17 A and Power Voltage (Vmp) 17.1 V. To obtain the maximum power of the sun, the module is static fixed in 10-20 N adjusting to the equator line. The measurement is conducted in Timah Manufacture Polytechnic which is situated in 1020' S and 1060 E. The output is observed by multimeter data logger for every hour average. The cable employed between solar module and the multimeter and the battery is NYA Eterna 2.5 mm2 450/750 V with SNI number 04-2698 SPLN 42, the long is 40 meter and have resistance about 0.6-0.7 W. The measurement output indicates that the maximum solar power is at 11.00 to 14.00 WIB. In these times, the current output is more than Imp of the Module. By calculating the average of energy received in a day, the energy received is 65%-75% of Imp. Therefore by mathematically calculation, the annual yield of current is about 4,982.68 Ampere and in 25 years will be around 124,566.90 Ampere. According to PLN statistic report in 2008, the average cost production in 2007 is Rp.706.62/KWH and the cost production of the solar energy is about Rp.440.819/KWH. This calculation is included the investment, overhead and 10% of inflation /year. By comparing to the regional minimum revenue (UMR) per month in 2008, the cost of investment for the solar power usage is about 6-7 times. Although break-even-point will be occurs in 10 years, the affordability of Indonesian for massive usage of solar power is still too hard and need funded by government and others funding groups. Keywords: Solar Cell, Cost-Effective, Poly-Crystalline-Silicone, Annual Yield